Systematic Literatur Review: Software Matematika Math Mechanixs Sebagai Media Belajar untuk Meningkatkan Kemampuan Komputasi Siswa - Fauziah Mawaddah Harefa; Yahfizham Yahfizham (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to systematically examine the use of Math Mechanixs software as a medium for learning mathematics to improve students' computational skills. The method used is Systematic Literature Review (SLR), with data sources obtained from various scientific databases such as Google Scholar, Garuda, DOAJ, and ResearchGate. The study was conducted by filtering articles based on inclusion and exclusion criteria, then analyzed to find patterns and effectiveness of the use of the software. The results of the review indicate that Math Mechanixs, with its 2D/3D graphic visualization features, equation editor, and scientific calculator, has great potential in helping students understand mathematical concepts more efficiently and interactively. In addition to increasing the speed and accuracy of calculations, this software also encourages the development of students' algorithmic and logical thinking skills. However, more empirical research is needed to strengthen these findings in the context of Indonesian education. This study recommends the integration of Math Mechanixs in mathematics learning with the support of teacher training and adequate supporting facilities.